Psychological Factors and Training Methods Affecting Chinese College Students’ Confrontational Training in Football Teaching - Gang Jin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study examines the application and psychological elements associated with antagonistic training in football instruction. The author conducts tests on the School of Management's Sports Teaching Department, and students enrolled in the football option class, separated into two experimental and two control groups. After 32 weeks of training at a rate of four hours per week, a significance test was performed on the exercise indices of the two groups of students. The control group's physical fitness indicators trail behind those of the experimental group, with substantial differences in the two indicators being 30m and 1500m; while the two indications of 100m and standing long jump have extremely significant discrepancies. The control group's football skill indicators trail behind the experimental group. The experimental group's antagonistic training influenced students' sprinting ability, lower limb explosiveness, and football abilities. Simultaneously, psychological development is critical in football training.